An Expedition to Geometry - Kumaresan, S. (Texts and Readings in Mathematics ;, 2005)
Including Affine and projective classification of Conics, 2 point homogeneity's of the planes, essential isometrics, non euclidean plan geometrics, in this book, the treatment of Geometry goes beyond the Kleinian views.